2014
DOI: 10.3941/jrcr.v8i7.2070
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Portal and systemic venous gas in a patient with perforated duodenal ulcer: CT findings

Abstract: Gas within the portal circulation has been known to be associated with a number of conditions most commonly mesenteric ischemia and necrosis. Systemic venous gas is described with few conditions and is mostly iatrogenic in nature. We describe a case of combined portal and systemic venous gas detected by computed tomography in a patient with perforated duodenal ulcer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Our findings on US are compatible with previous reports in adult cases that showed that the HH sign was diagnostic for DU (6,7). In previous reports, the presence of free air and variable amounts of free fluid were significant findings indicating perforated peptic ulcers (9)(10)(11). Free air is visualized as a reverberation, having a comet-tail appearance in the ultrasound (9, 10).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings on US are compatible with previous reports in adult cases that showed that the HH sign was diagnostic for DU (6,7). In previous reports, the presence of free air and variable amounts of free fluid were significant findings indicating perforated peptic ulcers (9)(10)(11). Free air is visualized as a reverberation, having a comet-tail appearance in the ultrasound (9, 10).…”
Section: Discussionsupporting
confidence: 91%
“…Free air is visualized as a reverberation, having a comet-tail appearance in the ultrasound (9, 10). Fam et al (11) reported a case of a perforated DU with pneumoperitoneum, where air in the portal and systemic venous systems was confirmed by CT. In our study, in the patient with a perforated DU, there was no evidence of free air, but a relatively large amount of free fluid was revealed on US.…”
Section: Discussionmentioning
confidence: 95%
“…To be specific, firstly, infection: gas-producing bacteria, such as Clostridium perfringens , Escherichia coli and Klebsiella pneumoniae , intrude into the intestinal wall or portal vein, which have bred, thus generating gas [6, 13]. Secondly, intestinal mucosal injury and increased enteric cavity pressure: intestinal gas can act under the action of increasing intestinal pressure in the presence of intestinal mucosal injury, which can thereby enter the portal vein system through the damaged mucosa [14]. Thirdly, mixed type: HPVG is the consequence of interaction of infection with mucosal injury [15].…”
Section: Discussionmentioning
confidence: 99%